Evangeliemandens Liv - Brand, Neil (Danish Silent Classics, 2004)
The young hothead Billy is drifting into a life of crime and has a violent quarrel with his girlfriend Nelly. The lay preacher John Redmond tells Billy his life's story. Many years before, he was a wealthy young man about town; he was enthralled by a seductive demimondaine, but was madly jealous of her other lovers. During a fight with one of them, he pulled a gun, and a stray bullet killed the woman. Sentenced to many years in jail, he repented and found faith with the help of the prison chaplain. He could leave the prison as a new and better man. Inspired by this story, Billy is filled with remorse, and he and Redmond manage to save Nelly, who is about to commit suicide. The two young people are united by Redmond. The sophisticated clair-obscur cinematography demonstrates the high standards of the Nordisk productions. The realistic depiction of contemporary prison conditions is striking, even if the solemn religiosity of the story may be off-putting to some. It is probably the best film made by Valdemar Psilander, Nordisk's biggest star: strong and strikingly handsome, he often portrays psychologically fragile, somewhat weak-willed men. Psilander is introduced with a wonderful vignette where he carefully studies the screenplay, and the three different phases of his character's development (roué, convict, preacher) appear before him. Psilander makes great play with both his usual man-about-town role and with the figure of the apparently faultless preacher, whose pious dedication springs from the awareness of his own grievous sins. [www.dfi.dk]